How to Succeed with Continuous Improvement : A Primer for Becoming the Best in the World - Ahlstrom, Joakim (New York McGraw-Hill Education, 2015)
"The all-you-need-to-know primer on continuous improvement--offering best practices presented in a comprehensive, detailed case study illustrating what works and what doesn'tHow to Succeed with Continuous Improvement takes the reader through a real-life case study of one organization's journey towards a world-class continuous improvement process. It provides practical advice on methods, tools, and leadership to help operations professionals set up, execute, and continuously build upon their organization's improvement work. The book offers specific advice and practical application on how to get all employees to give maximum contributions by using their ideas to improve the organization. Each chapter details part of the transformation story and then reflects on and analyzes each concept of continuous improvement illustrated. Joakim Ahlstrom is Head of Consulting for C2, a firm that helps companies establish continuous improvements that provide measurable results.
Include Illustration
Keywords: Success in business -- Total quality management -- Continuous improvement process